Historyk języka jako tropiciel śladów = Language historian as a traces stalker - Rejter, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article treats of various traces of a language past as a basic problem for a language historian. What is important, a language history is understood in a communication sense, as a history of language use. The author proposes three types of traces, which a historian of a language has at his disposal. These traces are: direct traces, indirect traces and reinterpreted traces. Regardless of whether the trace is more or less clear, the superior question is its usefulness and what the trace leads to.
Keywords: historia języka; historia; język polski; historiografia; language history; Polish language; history; historiography